Nanomedicines harnessing cGAS-STING pathway: sparking immune revitalization to transform ‘cold’ tumors into ‘hot’ tumors - Xiaohong Ying; Qiaohui Chen; Yongqi Yang; Ziyu Wu; Wan Zeng; Chenxi Miao; Qiong Huang; Kelong Ai (Molecular Cancer)
Abstract cGAS-STING pathway stands at the forefront of innate immunity and plays a critical role in regulating adaptive immune responses, making it as a key orchestrator of anti-tumor immunity. Despite the great potential, clinical outcomes with cGAS-STING activators have been disappointing due to their unfavorable in vivo fate, signaling an urgent need for innovative solutions to bridge the gap in clinical translation. Recent advancements in nanotechnology have propelled cGAS-STING-targeting nanomedicines to the cutting-edge of cancer therapy, leveraging precise drug delivery systems and multifunctional platforms to achieve remarkable region-specific biodistribution and potent therapeutic efficacy. In this review, we provide an in-depth exploration of the molecular mechanisms that govern cGAS-STING signaling and its potential to dynamically modulate the anti-tumor immune cycle. We subsequently introduced several investigational cGAS-STING-dependent anti-tumor agents and summarized their clinical trial progress. Additionally, we provided a comprehensive review of the unique advantages of cGAS-STING-targeted nanomedicines, highlighting the transformative potential of nanotechnology in this field. Furthermore, we comprehensively reviewed and comparatively analyzed the latest breakthroughs cGAS-STING-targeting nanomedicine, focusing on strategies that induce cytosolic DNA generation via exogenous DNA delivery, chemotherapy, radiotherapy, or dynamic therapies, as well as the nanodelivery of STING agonists. Lastly, we discuss the future prospects and challenges in cGAS-STING-targeting nanomedicine development, offering new insights to bridge the gap between mechanistic research and drug development, thereby opening new pathways in cancer treatment.